2017
DOI: 10.1186/s12939-017-0706-8
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities of outpatient and inpatient service utilization in China: personal and regional perspectives

Abstract: BackgroundChina’s health system has shown remarkable progress in health provision and health outcomes in recent decades, however inequality in health care utilization persists and poses a serious social problem. While government pro-poor health policies addressed affordability as the major obstacle to equality in health care access, this policy direction deserves further examination. Our study examines the issue of health care inequalities in China, analyzing both regional and individual socioeconomic factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 36 publications
7
57
1
Order By: Relevance
“…Present studies have shown that household income is beneficial to the use of inpatients in the rich, which is the dominant determinant of inequality in the utilization of inpatient services since more wealthy individuals are able to pay for and utilize more inpatient services [37][38][39]. But some studies have shown that the differences of health service utilization between income groups were not significant [40]. In this study, the average annual household income was divided into five levels and the differences in the inpatient service utilization among middle-aged and elderly females at different levels were not statistically significant.…”
Section: Discussionmentioning
confidence: 95%
“…Present studies have shown that household income is beneficial to the use of inpatients in the rich, which is the dominant determinant of inequality in the utilization of inpatient services since more wealthy individuals are able to pay for and utilize more inpatient services [37][38][39]. But some studies have shown that the differences of health service utilization between income groups were not significant [40]. In this study, the average annual household income was divided into five levels and the differences in the inpatient service utilization among middle-aged and elderly females at different levels were not statistically significant.…”
Section: Discussionmentioning
confidence: 95%
“…Most previous studies in China have focused on socio‐economic inequality in healthcare utilisation among the general population or among people with chronic diseases . Some studies have also examined the degree of CHE or health impoverishment at the sub‐national level or in rural areas in China .…”
Section: Introductionmentioning
confidence: 99%
“…According to Briggs et al (2012), Kununurra (rural Western Australia) residents with chronic LBP would have to travel more than 800 km to Darwin or more than 3,000 km to Perth to access the nearest centre providing multidisciplinary pain management services. In keeping with this idea, there is also other evidence to show that location of residence contributes to inequality of healthcare utilisation for health conditions (Zhu, Guo, Wang, Nicholas, & Chen, 2017) including LBP (Bath, Lawson, Ma, & Trask, 2018). In addition, the socioeconomic difference between the urban and rural populations contributes greatly to the variation in point of healthcare utilisation (Gebauer, Salas, & Scherrer, 2017;Olah, Gaisano, & Hwang, 2013;Plénet et al, 2010).…”
Section: Discussionmentioning
confidence: 86%